Waste to fuel mobile pyrolyser - Ruzinah, Isha; Rohayu, Jusoh; Hafizah, Ramli; Normardhati, Mustafa; Wan Mohd Hafizuddin, Wan Yussof; Khairunnaim, Azmi (2021)
Poor management of municipal waste leads to greenhouse gases and scarce of landfill